2007
DOI: 10.1645/ge-1045r.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of Spermiogenesis and the Spermatozoon of Crepidostomum Metoecus (Digenea: Allocreadiidae), a Parasite of Salmo Trutta (Pisces: Teleostei)

Abstract: Spermiogenesis and the spermatozoon of Crepidostomum metoecus, an intestinal parasite of brown trout Salmo trutta, were studied by transmission electron microscopy. Spermiogenesis begins with the formation of a differentiation zone in front of 2 centrioles associated by an intercentriolar body. Each centriole is linked to a striated rootlet, and gives rise to a flagellum. The rotation of flagella is greater than 90 degrees; their fusion with the median cytoplasmic extension is proximodistal and asynchronous. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Such a rotation, nevertheless, is relatively frequent in digeneans, in particular in species from the Fasciolidae, Dicrocoeliidae, Monorchiidae, Opecoelidae and Allocreadiidae (Ndiaye et al 2003a;Levron et al 2003Levron et al , 2004Agostini et al 2005;Quilichini et al 2007a, b). As indicated above, rotation is concluded to be present in G. catostomi and may be similar to that of K. armeniaca (Table I).…”
Section: Discussionmentioning
confidence: 91%
“…Such a rotation, nevertheless, is relatively frequent in digeneans, in particular in species from the Fasciolidae, Dicrocoeliidae, Monorchiidae, Opecoelidae and Allocreadiidae (Ndiaye et al 2003a;Levron et al 2003Levron et al , 2004Agostini et al 2005;Quilichini et al 2007a, b). As indicated above, rotation is concluded to be present in G. catostomi and may be similar to that of K. armeniaca (Table I).…”
Section: Discussionmentioning
confidence: 91%
“…Such spinelike bodies were described for the first time by Miquel et al (2000) in Opecoeloides furcatus (Opecoelidae). Other recent studies have shown the existence of spinelike bodies in Notocotylus neyrai (Ndiaye et al 2003b), Poracanthium furcatum (Levron et al 2004b), Fasciola gigantica (Ndiaye et al 2004), Dicrocoelium hospes (Agostini et al 2005), Troglotrema acutum (Miquel et al 2006), Crepidostomum metoecus (Quilichini et al 2007a), Nicolla wisniewskii (Quilichini et al 2007b), N. testiobliquum (Quilichini et al 2007c) and Paramphistomum microbothrium (Seck et al 2007). But in these species, except for the last one, the spinelike bodies are not located on the lateral expansion.…”
Section: Discussionmentioning
confidence: 95%
“…This rotation has been already observed in most of the studied digenean species (Table I). However, flagella in six others trematodes: Helicometra fasciata (Levron et al 2003), Fasciola hepatica (Ndiaye et al 2003a), Monorchis parvus (Levron et al 2004a), Dicrocoelium hospes (Agostini et al 2005), Nicolla wisniewskii (Quilichini et al 2007a) and Crepidostomum metoecus (Quilichini et al 2007b) undergo a rotation greater than 90°. The flagella of the first four species have the particularity of a rotation of 120° before fusion with the median cytoplasmic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case for T. taeniaeformis. Taking into account the recent observations of flagellar rotations of up to 120°in the Fasciolidae, Dicrocoeliidae, Monorchiidae, Opecoelidae and Allocreadiidae digeneans (Ndiaye et al 2003c;Levron et al 2003Levron et al , 2004Agostini et al 2005;Quilichini et al 2007a, b), and described in the caryophyllidean Wenyonia virilis and in the spathebothriidean C. truncatus (Bruňanská et al 2006, Miquel et al 2008), it appears that there may be a gradual reduction of the rotation angle until there is no rotation, a state that is considered the apomorphic condition of this character (Justine 1998(Justine , 2001.…”
Section: Spermiogenesismentioning
confidence: 95%